ASEAN GO PUBLIC COMPANIES’ STOCK SPLIT: CUMULATIVE ABNORMAL RETURN AND CUMULATIVE TRADING VOLUME ACTIVITY - Darsono, Caroline Illene Hari; Martono, Cyrillius; Memarista, Gesti (STIE Mahardhika, 2023)
The current study compares the differences between Cumulative Abnormal Returns (CAR) and Cumulative Trading Volume Activity (CTVA) for publicly traded companies that execute stock splits in the year 2021 on the ASEAN Stock Exchange. According to estimates and timelines, businesses listed on the ASEAN Stock Exchange in 2021 are not permitted to take additional corporate action. There are 47 companies using the sampling exchange in the countries of Indonesia, Malaysia, Philippines, Vietnam, Thailand, and Singapore. The data analysis methodology used by researchers is a different test through the Wilcoxon Rank Test. The first result from this study is that there is a difference in CAR before and after a stock split that is significant. In contrast, for the second result, there is no significant difference in the CTVA for the prior and subsequent stock split. Before the stock split happened, researchers discovered a bigger discrepancy in CAR. This shows that the market responded from time t-31 to time t-1. Due to a number of reasons, including the global influence of dominant data and patterns in investor behavior, there was no discernible difference in the CTVA.